Biosorbent Efficacy of Groundnut Husk for the Elimination of Chromium from the Effluent of Mojo Tannery Industry, Ethiopia - Kebru Tegegn; Zekeria Yusuf; J. M. Sasikumar; Kefelegn Gorfu (International Journal of Biomaterials)
The present study aimed to assess the effects of raw (RGNH), ethanol-extracted (EEGNH), and acid-treated (ATGNH) groundnut (Arachis hypogaea L.) husk for removal of chromium from tannery effluent from the Mojo tannery industry, Ethiopia. The effects of biosorbent dose, agitation speed, and contact time of heavy metal on biosorbent were measured. The percentage removal of chromium was examined by a flame atomic absorption spectrophotometer (FAAS). Functional group characteristics of the biosorbents were analyzed using Fourier transform infrared spectra (FTIR). The results indicated that at low doses (2 g), acid-treated groundnut husk (ATGNH) exhibited the highest removal efficiency (89.93%), whereas at a high dose (4 g), the raw groundnut husk (RGNH) has a potential removal efficiency (91.03%). The least removal efficiency was displayed by ethanol-extracted groundnut husk (EEGNH) (65.43%) at a dose of 3 g. Relating to the contact time, the highest chromium removal (94.41%) was exhibited by ATGNH with a 1-hour contact time. However, as contact time increased from 2 to 4 hours, there was a general decrease in the efficiency of biosorption. The removal of chromium by RGNH and EEGNH increased as contact time increased from 1 to 3 hours. The highest chromium removal (90.02%) was observed with ATGNH at 160 rpm agitation speed.